Meningkatkan Hasil Belajar IPS Kelas 5 SD Menggunakan Model PBL, Mind Mapping dan Talking Stick - Erly Noorliana, Khairil Anwar (CV.ITTC INDONESIA, 2023)
The purpose of this study was to determine teacher and student activities and improve student learning outcomes. This type of Classroom Action Research (PTK) was conducted in four sessions. The research environment was 17 students in semester 2 of SDN Kuin Selatan 1 Banjarmasin in 2022/2023. The types of data used are qualitative and quantitative, with qualitative data from teacher and student activity observation sheets and quantitative data from learning outcomes determined by group tests and learning assessments. The results of this study indicate that teacher activity in each session continues to increase from a score of 19